The Role And Importance Of Using Interactive Methods In The Education Of Professional Competence Criteria Of In-Service Teachers - Saiduradova Sitora Nabijonovna (Genius Journals, 2022)
This article discusses the form, methods, and means of interactive methods used in educating the professional competence of teachers in advanced training, their role, and significance, as well as the effectiveness of using these methods in educating such professional criteria for teachers as general professional, personal, communicative, selfdeveloping
Keywords: interactive methods; dispute; pedagogical training; argumentation